FAKTOR YANG BERPENGARUH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 1990-2020 - Arga Putri, Galeh Among; Islami, Fitrah Sari (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
This study analyzes the factors that contribute to economic growth in Indonesia in the period 1990-2020. Economic growth is the dependent variable applied in this study and the independent variable consists of imports, inflation, and household consumption. the method applied in this study is the Error Correction Model (ECM). From the results of the study, it is known that the variables of imports and household consumption have a positive and significant effect on economic growth, both in the long and short term. On the other hand, the impact of the inflation variable on economic growth is negative both in the long and short term.